Asymmetrical erythematous rash secondary to subcutaneous emphysema - Lata, Tahmina Jahan; Bull, Nicholas; Dick, Madeline; Anderson, Benjamin (International Surgery Journal, 2021)
Subcutaneous emphysema is a frequent post-operative complication. Although many cardiorespiratory complications associated with subcutaneous emphysema has been described, skin rashes have not been described as a complication. We present a case of asymmetrical erythematous skin rash secondary to subcutaneous emphysema. To the best of our knowledge this association has not been reported before. It is important to recognise cutaneous changes such as skin rash as a potential complication of subcutaneous emphysema and avoid inappropriate management and prolonged hospital stay. complication.